Prevalence of osteoarthritis patients in South Indian hospital - Viswanath, J.; Cheekavolu, Chakrapani; Dixit, Renu; Sankaraiah, S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Osteoarthritis is multifactorial in aetiology. Both systemic factors (e.g. age, sex, genes) and local factors (e.g. muscle weakness, joint deformity) appear to influence the risk of individual joints developing the disease. Methods: Total 60 patient’s prospective data was collected in S.V. Ayurvedic Medical College and Hospital. Collected data were family history, physical activity, illness, addiction, digestive power etc., in patients with osteoarthritis. Results: The study showed 53.33% of previous family history of osteoarthritis and 46.66% were no family history of osteoarthritis. 76.66% gradual disease onset and 23.33% were insidious onset. 100% were having joint pain with swelling. 50% were average digestive power, 36.66% good and 13.33% poor. 30% patients were having addiction of alcohol, 16.66% smoking and alcohol, 16.66% smoking, 3.33% tobacco and 33.33% were no addiction. 66.66% patients were having irregular bowel habit and 33.33% was regular. 41.66% sedentary, 40% active and 18.33% were moderately active. 40% illness was observed during the period of 0-6 months, 30% 1-2 years, 16.66% 6-12 months and 13.33% were 2-5 yrs. 60% cold season and 40% were other seasons. Conclusions: Present study demonstrated that, incidence of osteoarthritis was very high especially in earlier family history of osteoarthritis, gradual disease, joint pain, average digestive power, No addiction, bowel habit Irregular, sedentary, illness during the period of last 6 months and cold season patients.